Answer:
C
Step-by-step explanation:
By counting cause you can find your answer duh
2+4=6
6+-7=-1
Your answer would be negative 1 or -1
Answer: X=-7
Step-by-step explanation:
Using PEMDAS;
Step 1: Distribute the "3" in the part of the equation "3(x-2)"
3x - 6
Step 2: Consider the equation as a whole with the newly part of the equation from step 1, as it is a part of the equation
Therefore, re-written as,
3x - 6 + 48 = -3x
Step 3: Evaluate the re-written equation
Using basic mathematics skills, we can evaluate the following,
3x - 6 + 48 = -3x ➡ -6 + 48 = -6x ➡ 42 = -6x ➡ -7 = x
As shown, the answer is x=-7.
Lisa gave her sister 1/4, or one-fourth of her toy cars. Brainliest would really help!